Effect of selenate on treatment of glycerol containing wastewater in UASB reactors. (April 2023) - Logan, Mohanakrishnan; Tan, Lea Chua; Nzeteu, Corine Orline; Lens, Piet N.L.
Abstract: The effect of selenate on the removal of glycerol in up-flow anaerobic sludge blanket (UASB) reactors was investigated. Two UASB reactors, RControl and RSelenium, were operated at a hydraulic retention time of 48 h and an upflow velocity of 2 m/h at 37 °C. A GAL (glucose, acetate and lactate) and glycerol mixture were used as the only feedstock throughout the experiment for RControl . After acclimation to GAL and glycerol in the start-up period, RSelenium was additionally exposed to selenate (SeO4 2− ) concentrations from 1.43 to 71.49 mg/L (10–500 μM) in a stepwise manner. An average daily methane yield of about 150 mL/g COD, which was comparable with RControl, and 90% Se removal were achieved until 400 μM SeO4 2− . Simultaneously, SeO4 2− was reduced to elemental Se or metal selenide, supported by X-ray diffraction, as well as scanning and transmission electron microscopy. However, the methane production rapidly deteriorated when the influent SeO4 2− concentration was increased to 500 μM. The Se toxicity was evident from the reduction in the activity of Methanosaeta . This study showed that the SeO4 2− concentration, but not the COD/SeO4 2− ratio, governs the AD of selenate rich wastewaters. Graphical abstract: Image 1 Highlights: Selenate concentration, but not COD/selenate ratio, governs the anaerobic digestion process. Methane yield of 150 mL/g COD·d with 90% selenium removal until 400 μM selenate. Inhibition of Methanosaeta activity observed at 500 μM selenate. Increase in solids content and settling velocity suggests selenium facilitated sludge granulation. Elemental selenium and metal selenide biosynthesis observed from XRD, TEM, SEM and SEM-EDX.